Analysis of Stock Market Trends for Market Capitalization and Securities Management: An approach to Nepalese Stock Market - Karna, Santosh Kumar; Sahani, Suresh Kumar; Sharma, Dhiraj Kumar (Asian Journal of Early Childhood and Elementary Education, 2024)
Attraction towards share market is increasing day by day. Relevance for guiding people towards purchase and sale of share is also increasing everywhere in the world. Nepal is a poor country having well developed share market, but some sort of hurdles and technical disparities are still creating problems in operation of this market. Increasing economic crisis for last two years has made this market critical. Decrease in price of share is caused by increasing losses in business and industry at present. The main objective of the study is to examine the growth trend of the Nepalese securities market. It helps to analyze the trend of Nepalese stock market in terms of market capitalization, number of transaction, number of securities traded and number of securities listed and to examine the space of primary market growth in Nepal. this work is motivated by the works of (see[6-31]).